PARADIGMA KESEIMBANGAN ANTARA AKADEMIK DAN KESEJAHTERAAN SISWA: PERBANDINGAN SISTEM PENDIDIKAN JEPANG, DENMARK, DAN FINLANDIA - Anariska; Arri Rumiati; Heri Susanto; Kristina; Mena Lestari; Hasrita Lubis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze and compare the paradigm of balance between academic achievement and student well-being within the education systems of three OECD countries Japan, Denmark, and Finland. The primary objective is to explore how these nations interpret and implement the concept of equilibrium between academic demands and students’ emotional needs, as well as how their educational policies shape learners’ character and intrinsic motivation. The background of this study arises from the global disparity in educational orientations that often emphasize academic performance and testing outcomes while neglecting students’ psychological welfare, happiness, and holistic development. In many countries, excessive academic pressure has led to negative consequences such as stress, depression, and loss of learning motivation. Conversely, nations like Denmark and Finland demonstrate that prioritizing student well-being can foster meaningful and sustainable learning quality. This research adopts a qualitative approach using the library research method. Data were collected from national education policies, OECD reports, scientific publications, and previous studies. The data were analyzed through Comparative Qualitative Analysis (CQA) to identify similarities, differences, and underlying philosophical values in the educational paradigms of the three countries. The findings reveal that Japan emphasizes work ethics, discipline, and collective responsibility; Denmark prioritizes psychological welfare and learning autonomy; while Finland successfully integrates both through flexible curricula, non-competitive assessment systems, and high teacher professionalism. The implications of this study highlight the necessity for educational reform that balances academic demands with student well-being. The results conclude that an ideal educational paradigm should cultivate the development of whole individuals intellectually competent, emotionally fulfilled, and morally grounded.